Nurses' Work Methods Assessment Scale: a study of content validation - João Miguel Almeida Ventura-Silva; Maria Manuela Ferreira Pereira da Silva Martins; Letícia de Lima Trindade; Ana da Conceição Alves Faria; Sónia Cristina da Costa Barros; Ricardo Manuel da Costa Melo; Elaine Cristina Novatzki Forte; Olga Maria Pimenta Lopes Ribeiro (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To develop and validate the content of the Nurses' Work Methods Assessment Scale. Methods: Methodological study conducted between January and February 2022, based on the Quality Standards for Nursing Care and Imogene King's framework. A literature review was previously undertaken to design the scale. The content validation was carried out by 23 experts. Results: The initial version consisted of 40 items organized in four work methods identified in the literature. In the first dimension, from ten items, seven were considered, and one was reformulated. Seven of the initial ten items were considered in the second version. The third dimension consisted of seven items. In the fourth dimension, three items were reformulated, and three were excluded, leaving seven items. The final version ended with 28 items, whose Content Validity Index ranged between 0.83 and 1. Conclusions: The involvement of experts has become pivotal in the development and validation of the items, providing confidence to the continuity of psychometric procedures.